Cognitive Performance and the Alteration of Neuroendocrine Hormones in Chronic Tension‐Type Headache. Issue 1 (5th May 2017) - Qu, Ping; Yu, Jin‐Xia; Xia, Lan; Chen, Gui‐Hai
Abstract: Tension‐type headache (TTH) is the most prevalent primary headache. Chronic TTH (CTTH), the most serious form of TTH, is refractory, with a high socio‐economic burden. Research studies have shown patients with migraine often had cognitive impairment, but few studies have focused on the cognition in patients with CTTH. In this study, we assumed that patients with CTTH also have cognitive impairments, which are modulated by the neuroendocrine state. Participants were recruited, including patients with CTTH and healthy controls. Cognitive ability was evaluated using the Montreal Cognitive Assessment and the Nine Box Maze Test. The administration of neuroendocrine hormones has been established to be associated with cognitive performance, and we detected the hormonal changes in the hypothalamus–pituitary–adrenal axis, the hypothalamus–pituitary–thyroid axis, and gonadotropin‐releasing hormone. These results showed that compared to the controls, significant cognitive impairment and neuroendocrine dysfunction were present in the patients with CTTH. We also assessed the correlations between the neuroendocrine hormones and Pittsburgh Sleep Quality Index score, 17‐term Hamilton's Depression Scale score, pain intensity, and duration of pain to determine whether the neuroendocrine hormones had any associations with these symptoms of CTTH. These results showed that changes in neuroendocrine hormones were involved in these symptoms of CTTH. Intervention with the neuroendocrine state may be a strategy for CTTH treatment.